1985
DOI: 10.1111/j.1745-9125.1985.tb00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Crime as Hazard: Perceptions of Risk and Seriousness*

Abstract: The study of crime suffers from an inattention to the social consequences of criminal acts. Conceiving crimes within the larger context of '%hazard, " data are reported on the relative seriousness of conventional and white-collar crimes, as well as other hazards, using a sample of Washington state respondents. The results indicate that there is an inverse relationship between the perceived likelihood of a hazard and its seriousness. Generally, the more immediate the threat of a hazard, such as white-collar cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…For example, murder, rape and personal theft may have stronger effects on the fear of crime than larceny and auto theft. Hence, the total crime rate that was used in this research might not be sophisticated enough to examine the association between the prevalence of crime in the district and the residents’ health condition 23. However, when we conducted a post-hoc analysis using a different measure, ‘5 index crime rate’, which includes five major serious crimes (ie, murder, robbery, rape, assault and theft) that has been adopted by the Korean police to indicate violent crime rate, still we could not find association with residents’ self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…For example, murder, rape and personal theft may have stronger effects on the fear of crime than larceny and auto theft. Hence, the total crime rate that was used in this research might not be sophisticated enough to examine the association between the prevalence of crime in the district and the residents’ health condition 23. However, when we conducted a post-hoc analysis using a different measure, ‘5 index crime rate’, which includes five major serious crimes (ie, murder, robbery, rape, assault and theft) that has been adopted by the Korean police to indicate violent crime rate, still we could not find association with residents’ self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, additional research found that a fear of crime measure was only significant under certain circumstances (Cohn, Barkan, & Halteman, 1991). Another study comparing public opinion on different types of crime revealed greater perceived risk of white-collar crime victimization than street crime, natural hazard, and nuisance crime victimization (Meier & Short, 1985). On the other hand, offenses that caused greater personal injury or property damage were perceived to be the most serious.…”
Section: Public Opinion Research On White-collar Crimementioning
confidence: 97%
“…"Toward a Control Theory of White-Collar Offending" Wayward Capitalists "'On the Causes of "White-Collar Crime" "" Crimes of the Middle Classes E, Reactions of the Criminal Justice System Edethertz (1970) The Nature, Impact and Prosecution of White- Katz (1980) Hagan, Nagel-Bernstein, and Albonetti (1980) Levi (1987) Mann (1985 Wheeler, Mann, and Sarat (1988) F. Public and Media Reactions Cullen, Link, andPolanzi (1982) Evans andLundman (1983) Meier and Short (1985) Newman (1957) Swigert andFarrell (1980-1981) scholars. The criteria for including a given work were not haphazard, however; a high level of interrater reliability existed between us, and the titles we selected are cited regularly by other scholars (see, for example, the references to the essays in Schlegel and Weisburd 1992).…”
Section: Theft By Employees Prescription For Profitmentioning
confidence: 98%